2012
DOI: 10.1117/1.jbo.17.6.066008
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal optical imaging for detecting breast cancer

Abstract: Abstract. The goal of the study was to evaluate wide-field and high-resolution multimodal optical imaging, including polarization, reflectance, and fluorescence for the intraoperative detection of breast cancer. Lumpectomy specimens were stained with 0.05 mg∕ml aqueous solution of methylene blue (MB) and imaged. Wide-field reflectance images were acquired between 390 and 750 nm. Wide-field fluorescence images were excited at 640 nm and registered between 660 and 750 nm. High resolution confocal reflectance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
(39 reference statements)
1
24
0
Order By: Relevance
“…The mean fluorescence polarization of normal, fibrocystic, and cancerous areas measured over all samples in this study was found to be 0.03 AE 0.01, 0.02 AE 0.01, and 0.06 AE 0.02, respectively. The fluorescence polarization values found for normal and cancer tissue in this study are in good accordance with previously measured values from our earlier study (15). Higher fluorescence polarization of cancer with respect to benign tissue was measured in all the samples.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The mean fluorescence polarization of normal, fibrocystic, and cancerous areas measured over all samples in this study was found to be 0.03 AE 0.01, 0.02 AE 0.01, and 0.06 AE 0.02, respectively. The fluorescence polarization values found for normal and cancer tissue in this study are in good accordance with previously measured values from our earlier study (15). Higher fluorescence polarization of cancer with respect to benign tissue was measured in all the samples.…”
Section: Resultssupporting
confidence: 81%
“…For correlating optical and histologic images and for evaluating cancer contrast in the optical images, the tumor and normal areas were outlined in the optical images of each specimen, exactly as they present in histopathology. This procedure was described in detail elsewhere (15,16,35,36). In short, cancerous and normal regions were outlined by a pathologist in digitized histopathology slides.…”
Section: Evaluation Of Tumor Contrast In Optical Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Confocal microscopy is an emerging technology for rapid imaging of freshly excised tissue without the need for frozen-or fixed-section processing. Initial studies have described the major findings of invasive breast cancers using fluorescence confocal microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…These include methodology based on Raman spectroscopy (10,11), scanning in situ spectroscopy and mapping of whole specimens (12), combined diffuse reflectance spectroscopy and intrinsic autofluorescence (10,13), or multimodal optical imaging (14). These studies have been exploratory and have examined and mapped tissue distribution in whole excised specimens ex vivo.…”
Section: Introductionmentioning
confidence: 99%